2008
DOI: 10.1016/j.jaci.2008.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Prematurity, chorioamnionitis, and the development of recurrent wheezing: A prospective birth cohort study

Abstract: We found a strong joint effect of prematurity and chorioamnionitis on early childhood wheezing. This effect was stronger in African American subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 42 publications
6
81
2
Order By: Relevance
“…[16][17][18][19][20][21][22] Mechanistically, it has been proposed that chorioamnionitis, because of the associated proinflammatory state and heightened immune response, might play a role in asthma development for infants born preterm. 20,29 The few studies of late prematurity and the development of asthma showed mixed results. Using survey data from a nationally representative sample, Abe et al 24 did not find an association with late-preterm birth when asthma was assessed on the basis of caregiver reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22] Mechanistically, it has been proposed that chorioamnionitis, because of the associated proinflammatory state and heightened immune response, might play a role in asthma development for infants born preterm. 20,29 The few studies of late prematurity and the development of asthma showed mixed results. Using survey data from a nationally representative sample, Abe et al 24 did not find an association with late-preterm birth when asthma was assessed on the basis of caregiver reports.…”
Section: Discussionmentioning
confidence: 99%
“…An association between extreme preterm birth and chronic respiratory morbidity, including asthma, has been established. [16][17][18][19][20][21][22] However, most studies of late prematurity and respiratory morbidity have focused on short-term outcomes, such as respiratory distress syndrome, transient tachypnea of the newborn, and transfer to the NICU for mechanical ventilation. 3,4,10,23 Few studies have focused on the impact of late prematurity on longterm respiratory outcomes, such as the development of asthma.…”
mentioning
confidence: 99%
“…54,55 In a trial of postnatal hydrocortisone, chorioamnionitis was not associated with changes in the use of supplemental oxygen, bronchodilators or steroids at 18 to 22 months. 54 However, Kumar et al 55 recently reported an association between chorioamnionitis and both recurrent wheezing and physician-diagnosed asthma. This suggests that intrauterine exposure to inflammation may indeed have long-term adverse respiratory effects.…”
Section: Lungsmentioning
confidence: 99%
“…Mast cells in the lower airways contribute to the development of asthma and allergic diseases (26). Mast cells are of interest because of a possible relation between chorioamnionitis, preterm birth, and the development of asthma later in life (27,28). Mast cell activation results in degranulation, leading to the rapid release of inflammatory mediators, such as histamine, proteoglycans, and cytokines, which stimulate the recruitment of other inflammatory cells (29).…”
Section: Effects Of Lps As Gestation Advancesmentioning
confidence: 99%